The influence of yard trucks on berth operations in smaller container terminals - Stojaković, Maja (Array, 2019)
Nowadays smaller container terminals are facing an increase in traffic and ship sizes and are consequently subject to extreme pressure form ship-owners that require rapid and efficient transhipment operations in the port, the achievement of which is only possible with the assignment of the proper type and number of quay cranes to each ship and with a good level of synergy between the cranes and the transfer mechanisation. The latter has a significant impact on the cranes working and waiting times and affects the entirety of berth operations. Existing terminals that cannot afford to invest in new modern horizontal transport technologies are most commonly using yard trucks that provide less efficient port transfer operations. That is why in the paper a simulation approach has been used in order to determine how a different number of yard trucks assigned to a single quay crane can affect the productivity of that crane and the productivity of the whole berth subsystem.